THE Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2019-2022 - Eka Nuzulia Putri; G Anggana Lisiantara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to test and analyze the influence of Good Corporate Governance such as the size of the board of commissioners, independent board of commissioners, institutional ownership,managerial ownership and audit commitee on company value. The population used in this research is mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. This type of research uses a quantitative approach using secondary data obtained from the company’s annual report. Sample selection was carried out using a purposive sampling method so that 113 samples of mining companies were obtained as research samples based on predetermined criteria. The analytical method used in the documentation method using SPSS 22. The result of the study show that the size of the board of commissioners has a significant positive influence on company value, the independent board of commissioners has no influence on the value of the company, institutional ownership has no influence on the value of the company, managerial ownership has no influence on the value of the company. Influence on company value. Has an influence on company value, and the audit committee has no influence on company value.